Associations between respiratory pathogens and lung function in primary ciliary dyskinesia: cross-sectional analysis from the PROVALF-PCD cohort - Rubbo, Bruna; Kant, Avni; Zhang, Kewei; Allegorico, Annalisa; Basilicata, Simona; Boon, Mieke; Borrelli, Melissa; Calogero, Claudia; Carr, Siobhán B; Carroll, Mary; Constant, Carolina; Castillo Corullón, Silvia; et al. (ERJ open research, 2024)
INTRODUCTION: Respiratory pathogens are frequently isolated from airway samples in primary ciliary dyskinesia (PCD) patients. Few studies have investigated associations between these pathogens and lung function, with current management based on evidence from cystic fibrosis. We investigated the association between commonly isolated respiratory pathogens and lung function in PCD patients. METHODS: Using a cross-sectional design, we prospectively collected clinical and concurrent microbiology data from 408 participants with probable or confirmed PCD, aged ≥5 years, from 12 countries. We used Global Lung Function Initiative 2012 references to calculate forced expiratory volume in 1 s (FEV1) z-scores. For 351 patients (86%) with complete data, we assessed the association of the four most frequently isolated pathogens with lung function by fitting multilevel linear models with country as random intercept, adjusted for age at diagnosis, age at lung function, use of antibiotic prophylaxis and body mass index z-scores. RESULTS: Individuals with Pseudomonas aeruginosa growth in culture had significantly lower FEV1 z-scores (β= -0.87, 95% CI -1.40- -0.34), adjusted for presence of Haemophilus influenzae, methicillin-sensitive Staphylococcus aureus and Streptococcus pneumoniae, and for covariates. When stratified by age, associations remained strong for adults but not for children. Results were similar when ciliary defects by transmission electron microscopy were included in the models and when restricting analysis to only confirmed PCD cases. CONCLUSIONS: We found that P. aeruginosa was associated with worse lung function in individuals with PCD, particularly adults. These findings suggest that it is prudent to aim for P. aeruginosa eradication in the first instance, and to treat exacerbations promptly in colonised patients.